Children's (Mis)understanding of the Balance Beam (Online Edition) - Filion, Virginie M. L.; Sirois, Sylvain (Frontiers in Psychology, 2021)
The balance-scale task, proposed by Inhelder and Piaget, illustrates children understanding of weight-distance relationships. Piaget used the clinical interview method in order to investigate children’s reasoning. Over the last five decades, Siegler’s Rule-Assessment Approach has been used to explain children reasoning in the balance-scale task according to rules children would use to solve the task. However, this approach does not take into account some key perceptual properties of the task. This study evaluates whether different task demands would alter children’s errors. Forty children (twenty children aged 4-5 years and twenty children aged 9-10 years) predicted the movement of both arms of 16 balance-scale problems administered online. Nine 4-5-year-olds produced non-plausible responses whereas none of the 9-10-year-olds provided non-plausible responses. These results seem to indicate a basic misunderstanding of the scale from younger children, a misunderstanding that eludes traditional measures used with this task.